Assessment of the potential toxic of naringenin nanoparticles using ex vivo and in silico models - G. B. Costa; B. F. Rossi; B. P. M. Oliveira; D. E. Santo; F. V. Leimann; A. L. Romero; A. P. Peron; O. H. Gonçalves (Brazilian Journal of Biology)
Abstract Naringenin is a flavonoid known for its anti-inflammatory, antineoplastic, antiatherogenic, and antioxidant properties. However, it has poor technological characteristics and limited bioavailability, which hinder its use in food applications. Nanoencapsulation could address these limitations, but safety concerns regarding nanoengineered bioactives need to be resolved before they can be effectively utilized as food additives. The objective of this study was to evaluate the potential cytotoxic, genotoxic, and mutagenic effects of both free and encapsulated naringenin through in vivo experiments using Allium cepa L. roots, along with pharmacokinetic and molecular docking analyses. The results showed that naringenin nanoparticles did not produce significant changes in the cell division index of meristematic cells in A. cepa roots. Additionally, no significant alterations in the mitotic spindle or chromosomal breaks were observed. Molecular docking studies indicated that naringenin effectively binds to the active site of the catalase enzyme (CAT) in a competitive manner, while it attaches to a site away from the active site of superoxide dismutase (SOD2), demonstrating a non-competitive interaction. ADMET property assessments suggested that naringenin exhibits relatively low toxicity and has favorable molecular characteristics for oral administration. In summary, this study supports the potential of naringenin, particularly in its nanoencapsulated form, as a safe and effective ingredient for functional foods, provided that safety concerns regarding nanoencapsulation are adequately addressed.